Influence of brain region of interest location for apparent diffusion coefficient maps calculation for reference values to be used in the in vivo characterization of brain tumors in magnetic resonance images - Souza, Edna M.; Castellano, Gabriela; Costa, Eduardo T. (Revista Brasileira de Física Médica, 2015)
In general, pathologic processes, such as neoplasic cell changes, tend to alter the magnitude of structural organization by destruction or reorganization of membranous elements or by a change in cellularity. These changes will also have an impact on proton mobility, which can be followed up by DWI (diffusion weighted magnetic resonance imaging). From DWI is obtained the ADC (apparent diffusion coefficient) map, which is a representation of the magnitude of water diffusion at the points of a given region of interest (ROI). The purpose of this study was to assess the variation of ADC values in different brain ROIs of normal subjects, using a computer tool previously developed. The aim of this assessment was to verify whether ADC values could be used to differentiate between normal subjects and patients with multiform glioblastoma (a high-grade glioma) and meningioma. ADC maps were calculated for 10 controls, 10 patients with glioblastoma and 10 with meningioma. For controls, mean ADC values were calculated for 10 different ROIs, located in the same places where the tumors were present in the patients. These values were then averaged over ROIs and over subjects, giving a mean ADC value of (8.65±0.98)x10-4 mm2 /s. The mean ADC values found for brain tumors were (5.03±0.67) x10-4 mm2 /s for meningioma and (2.83±0.45)x10-4 mm2 /s for glioblastoma. We concluded that the ROIs used for computing brain ADC values for controls were not essential for the estimation of normal reference ADC values to be used in the differentiation between these types of tumors and healthy brain tissue